1994
DOI: 10.1515/pteridines.1994.5.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Methanopterin in Methanobacterium thermoautotrophicum

Abstract: SummaryThe early steps in the biosynthesis of methanopterin in Methanobacterium thennoautotrophicum were analyzed by in vivo incorporation experiments of DC labeled precursors and by enzymatic studies. M thennoautotrophicum was grown in mineral medium supplemented with l3C-Iabeled acetate, pyruvate, or methionine. Methanopterin was isolated from the cells, and the I3.C-Iabeling pattern was determined by IH-and 13C_ NMR spectroscopy. The labeling patterns of amino acids and nucleosides were also determined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 16 publications
(34 reference statements)
1
29
0
Order By: Relevance
“…The primers that corresponded to the known transposon sequence, HOPS1 and HOPS2, were taken from Bardarov et al (5). The random primer Semi-rand 2-1 was independently developed, but Semi-rand 4 was the same as (13,22,38), and including the role of 2-phospholactate proposed by Graupner and White (17). primer 4 of Chun et al (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primers that corresponded to the known transposon sequence, HOPS1 and HOPS2, were taken from Bardarov et al (5). The random primer Semi-rand 2-1 was independently developed, but Semi-rand 4 was the same as (13,22,38), and including the role of 2-phospholactate proposed by Graupner and White (17). primer 4 of Chun et al (7).…”
Section: Methodsmentioning
confidence: 99%
“…The pathway by which F 420 is made has been explored with labeling approaches in methanogens (13,22,38). Also, recent enzymatic work with methanogens has shown that 2-phospholactate serves as a precursor of the lactyl and phosphate groups of F 420 (17).…”
mentioning
confidence: 99%
“…4, amino acids were isolated by chromatographic procedures as described in ref. 30, and 1 H and 13 C NMR spectra were recorded as described in ref. 4.…”
mentioning
confidence: 99%
“…The Archaea M. thermoautotrophicum and Halobacterium sp., the green alga Scenedesmus acutus, and the cyanobacterium Synechocystis sp. use F 420 in photolyase (16,17,26,38).In M. thermoautotrophicum, the pathway by which F 420 is made has been studied with labeling (15,23,45) and enzymatic approaches (19), which have allowed development of a hypothetical pathway, an overview of which is shown in Fig. 1B.…”
mentioning
confidence: 99%